(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In today’s digital educational landscape, the development of electronic resource collections in academic libraries holds significant importance. These collections not only offer extensive scientific information but also facilitate interactive and distance learning processes. By providing rapid and convenient access to educational materials through digital platforms, databases, and e-books, electronic resource collections empower users to efficiently locate and utilize information. This advancement is poised to elevate the scientific and creative endeavors of both students and academic staff, thereby enhancing the overall quality and effectiveness of education. The primary objective of this study is to analyze the process of developing electronic resource collections for academic libraries within the context of the digital educational environment. It seeks to explore the scientific and practical dimensions involved in selecting, acquiring, and subscribing to electronic resources. Furthermore, the study aims to identify the criteria and methodologies employed in this process, assess their effectiveness, and formulate recommendations for improvement. To conduct this research, various methods were examined and analyzed. To ensure comprehensive coverage and convenience for respondents, the online survey method was selected as the principal research approach. Four distinct surveys were designed to address different facets of the research objectives. These surveys focused on the selection criteria influencing decisions regarding the procurement of electronic resources, the strategies employed by specialists in forming electronic resource collections, and the criteria used to evaluate their effectiveness. All these aspects were thoroughly investigated and incorporated into the research. Based on the findings derived from this study, a series of recommendations were formulated. Proposals were developed to tackle the challenges associated with the selection of electronic resources and the enhancement of their collections in university libraries across Uzbekistan.